Vibration and Stability of 3000-hp, Titanium Chemical Process Blower - Les Gutzwiller; Mark A. Corbo (International Journal of Rotating Machinery)
This 74-in-diameter blower had an overhung rotor design of titanium construction, operating at 50 pounds per square inch gauge in a critical chemical plant process. The shaft was supported by oil-film bearings and was directdriven by a 3000-hp electric motor through a metal disk type of coupling. The operating speed was 1780 rpm. The blower shaft and motor shaft motion was monitored by Bently Nevada proximity probes and a Model 3100 monitoring system.